(untitled) (Revista Cocar, 2012)
As autoras se propõem a refletir sobre a formação de professores para atuar com e na diversidade, levando em consideração as mudanças decorrentes de um mundo globalizado, exigindo uma nova maneira de conceber a prática docente nos espaços educativos. Palavras-chave: Formação de professores. Diversidade. Multiculturalismo. Espaços educativos." Teacher training to act with / in diversity: a challenge of the contemporary The authors propose to reflect about the training of teachers to work with and in diversity, taking into account changes resulting from a globalized world requires a new way of thinking about teaching practice in educational spaces. Keywords: "Teacher training. Diversity. Multiculturalism. Educational spaces. "